Design and modeling of inductors, capacitors and coplanar waveguides at tens of GHz frequencies - Pour Aryan, Naser; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
This book describes the basic principles of designing and modelling inductors, MIM capacitors and coplanar waveguides at frequencies of several tens of GHz. The author explains the design and modelling of key, passive elements, such as capacitors, inductors and transmission lines that enable high frequency MEMS operating at frequencies in the orders of tens of GHz.
Introduction -- RF MEMS Process of Fraunhofer ISiT -- Designing Inductors -- Modeling the Coplanar Line -- DC-Block Modeling -- Design-Kit Programming -- Summary.
Electronic reproduction.
Keywords: Electric inductors -- Design and construction; Radio frequency integrated circuits -- Design and construction; Radio wave propagation; Wave guides; Wave equation; Electronic books